2011
DOI: 10.1016/j.jinsphys.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional sensitivity of fifth instar prothoracic glands in the tobacco hornworm, Manduca sexta

Abstract: The tobacco hornworm, Manduca sexta, has been a useful model for studying insect endocrinology. In M. sexta the majority of growth occurs during the fifth (final) larval stage. This growth is concurrent with endocrine changes that lead to a metamorphic molt. Past research has focused on the interplay of three growth hormones: juvenile hormone (JH), prothoracicotropic hormone (PTTH) and ecdysone, in regulating metamorphosis. The prothoracic glands, source of ecdysteroid molting hormones in insects, play a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…In addition, our previous study showed that insulin signaling is involved in growth and ecdysteroidogenesis of prothoracic glands (Gu et al, 2009). Insulin signaling in relation to the growth and secretory activity of Manduca prothoracic glands was also recently demonstrated (Walsh and Smith, 2011). Both bovine insulin and bombyxin (an insulin-like peptide in B. mori) also activate TOR signaling in silkworm prothoracic glands (Gu, unpublished data).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, our previous study showed that insulin signaling is involved in growth and ecdysteroidogenesis of prothoracic glands (Gu et al, 2009). Insulin signaling in relation to the growth and secretory activity of Manduca prothoracic glands was also recently demonstrated (Walsh and Smith, 2011). Both bovine insulin and bombyxin (an insulin-like peptide in B. mori) also activate TOR signaling in silkworm prothoracic glands (Gu, unpublished data).…”
Section: Discussionmentioning
confidence: 87%
“…Hence the glands were not incubated with trachea in an air-filled condition. Similar in vitro protocols are routinely used for assays of ecdysone secretion by insect prothoracic glands, for incubation periods ranging in length from 2 to 24 hr (Bombyx mori (Gu et al, 2009;Mizoguchi and Kataoka, 2005), Pseudaletia separata (Komiya et al, 2001), Rhodnius prolixus (Vafopoulou and Steel, 1998), M. sexta (Bollenbacher et al, 1984;Walsh and Smith, 2011;Watson et al, 1987)). …”
Section: Nitric Oxide/hypoxia Incubationmentioning
confidence: 99%
“…10 ll of sample were analyzed by procedures as previously described (Walsh and Smith, 2011;Warren et al, 1984). The ecdysone antibody was produced in rabbits against an ecdysone-22-succinyl thyroglobulin synthesized by Dr. D.H.S.…”
Section: Ecdysone Radioimmunoassaymentioning
confidence: 99%
“…Coordination of growth within and among tissues and organs then is mediated by the insulin/insulinlike growth factor (IGF) pathway. In Manduca the prothoracic glands grow during the final instar, and this growth is dependent on amino acids and TOR signaling (42,43). Accompanying the growth is an increased capacity to secrete ecdysone in response to PTTH, and starvation for the first 2 d of the fifth instar strongly suppresses this response and increases transcript levels of the insulin receptor and 4E-binding protein (4EBP) (a translation inhibitor) (42).…”
Section: Discussionmentioning
confidence: 99%
“…In Manduca the prothoracic glands grow during the final instar, and this growth is dependent on amino acids and TOR signaling (42,43). Accompanying the growth is an increased capacity to secrete ecdysone in response to PTTH, and starvation for the first 2 d of the fifth instar strongly suppresses this response and increases transcript levels of the insulin receptor and 4E-binding protein (4EBP) (a translation inhibitor) (42). Injection of insulin, however, was unable to rescue ecdysone production by the glands although it rescued the starvation-induced deficits in protein synthesis.…”
Section: Discussionmentioning
confidence: 99%